IRON-FORTIFIED SYNBIOTIC FERMENTED MILK WITH TEMPEH EXTRACT TO ENHANCES PROPIONIC ACID, BUTYRIC ACID, AND NON-PATHOGEN MICROBIOME IN ANEMIC WISTAR RAT - Mohammad Juffrie; Siti Helmyati (Media Gizi Mikro Indonesia, 2020)
Background. Anemia, as a global public health problem, needs to be solved. The previous study by the researcher found the potency of iron-fortified synbiotic fermented milk with tempeh extract as an alternative to overcome anemia. Objective. This study aims to determine the effects of iron-fortified synbiotic fermented milk with tempeh extract towards short-chain fecal fatty acids (SCFAs) and fecal microbiota. Method. The study was a randomized controlled trial with three groups, consisting of 8 anemic Wistar rats. The groups made into anemia within 17 days.The groups treated as follows: group NA: fermented milk with tempeh extract fortified by NaFeEDTA, group FE: fermented milk with tempeh extract fortified by FeSO4 , and group KO: fermented milk with tempeh extract without fortification. SCFAs and microbiota of the rat’s feces determined using the Total Plate Count method. SCFAs were measured after the intervention, while fecal microbiota was measured before and after the intervention. One-way ANOVA was used to measure the difference between NA, FE, and KO groups with post hoc test Bonferroni. Results. There was a significant mean difference between propionic and butyric acid between NA and FE groups and the KO group. The highest Lactobacilli number was in the FE group, while Bifidobacteria and Enterobacteriaceae were highest in the KO group. Meanwhile, the NA group had the highest Escherichia coli number. Conclusion. Iron fortification has positive effects on increasing the production of SCFAs in the gut. Prebiotics and probiotics have positive effects on pathogenic bacteria. Further study is needed to determine the effects of iron-fortified synbiotic fermented milk with tempeh extract in human.